KATA FATIS PENANDA KETIDAKSANTUNAN PRAGMATIK DALAM RANAH KELUARGA - R. Kunjana Rahardi; Yuliana Setyaningsih; Rishe Purnama Dewi (Sunan Kalijaga State Islamic University Yogyakarta, 2014)
One of the pragmatic markers, which shows language impoliteness, is classified in phatic category. This research aims to analyze the phatic discourse particles serving as pragmatic markers of impoliteness. Therefore, the data in this research are the utterances containing phatic discourse markers showing linguistic impoliteness taken from the family of farmers, traders, fishermen, teachers, and noblemen. The data were gathered by employing the listening and speaking methods. The data gathering techniques are the recording and transcribing. The data are classified and analyzed using contextual method. This research indicates that there are 11 categories of phatic discourse markers showing pragmatic impoliteness. They are phatic markers of “kok”, “ah”, “hayo”, “mbok”, “lha”, “tak”, “huu”, “iih”, “woo”, “hei”, and “halah”. Every phatic category conveys a specific intention which is different from other phatic discourse markers.